Process planning for 8-axis robotized laser-based direct metal deposition system: A case on building revolved part. (April 2017) - Ding, Yaoyu; Dwivedi, Rajeev; Kovacevic, Radovan
Abstract: Laser-based direct metal deposition (LBDMD) is a promising additive manufacturing technology that is well suited for production of complex metal structures, low-volume manufacturing, and high-value component repair or modification. It finds broad application in the automotive, biomedical, and aerospace industries. The Research Center for Advanced Manufacturing (RCAM) at Southern Methodist University is developing a robot controlled LBDMD system that couples a 6-axis robot arm with an additional 2-axis tilt and rotatory positioning system. The system simplifies the process planning of multiple-directional deposition for complex parts and reduces production time. This paper describes the printing process specific to complex revolved parts. Taking advantage of the coupled 2-axis tilt and rotatory system, a hybrid slicing method is developed to map the overhanging structures of a revolved part to be at a planar base. Consequently, the traditional path planning strategies are applicable to generate the tool-path for the mapped structures. The method is successfully applied to build a propeller. Highlights: An 8-axis robotized laser-based direct metal deposition system is developed. The process planning is developed to build the complex revolved parts. The hybrid slicing method maps the overhanging structures to a planar base. A propeller was printed to verify the performance of the process planning.